The Influence of Fear of Missing Out and Self Control on the Financial Behavior of Kpop Fans in Palopo City - Azzahra, Andi Mutiara; Hapid, Hapid; Usman, Halim (Journal of Applied Business, Taxation and Economics Research, 2025)
The phenomenon of Fear of Missing Out is now increasingly common, especially among lovers of popular culture such as Kpop. The purpose of this study is to analyze how Fear of Missing Out and self-control ability affect the financial behavior of KPop fans in the Palopo City area. The methodology of this study uses a quantitative approach by utilizing primary data collected directly through a questionnaire. The questionnaire contains a number of statements answered by the respondents. The population in this study was 684 people and the sampling technique was random sampling of 88 respondents using the slovin formula. The data collection technique in this study was through the distribution of questionnaires online using google form. Data analysis used various methods including validity tests, reliability tests, multiple linear regression analysis, t-tests, f-tests, determination coefficient tests with the help of the SPSS program. The findings of the study showed that there was a positive influence of Fear of Missing Out on the financial behavior of KPop fans in Palopo City, self-control had a positive effect on the financial behavior of KPop fans in Palopo City.